Physical and Emotional Burden of Rheumatoid Arthritis in Saudi Arabia: An Exploratory Cross-Sectional Study - Omair MA (Dove Medical Press, 2020)
Mohammed A Omair,1 Alper Erdogan,2 Nicole Tietz,3 Rieke Alten4 1Division of Rheumatology, Department of Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Medical Affairs Department, Eli Lilly and Company, Riyadh, Saudi Arabia; 3Eli Lilly and Company, Indianapolis, IN, USA; 4Schlosspark-Klinik University Medicine, Berlin, GermanyCorrespondence: Rieke AltenSchlosspark-Klinik University Medicine, Heubnerweg 2, Berlin 14059, GermanyTel +49 30 3264-1325Fax +49 30 3264-1324Email rieke.alten@schlosspark-klinik.dePurpose: The aim of this study was to better understand the physical and emotional impacts of rheumatoid arthritis (RA) on the lives of patients in Saudi Arabia, and to determine whether there are any discrepancies between how healthcare providers (HCPs) perceive the feelings of patients with RA and how patients actually feel.Patients and Methods: An online survey of adults with RA and HCPs was conducted in Saudi Arabia between January and June 2018. The survey used closed-ended questions with nominal and interval scales to cover relationships with others, ability to work and career progression, ability to perform normal activities, and aspirations for the future.Results: In total, 85 patients and 24 HCPs were surveyed. Patients were more likely than HCPs to feel that the people around them understood the emotional and physical impacts of RA (emotional impact understood: 67% of patients vs 42% of HCPs; physical impact understood: 61% vs 38%, respectively). Additionally, a larger proportion of younger (aged < 40 years) than older patients (aged 40– 59 and ≥ 60 years) felt that these impacts were not understood by others. For patients, the greatest barrier to working was difficulty using hands (52% vs 41% of HCPs), whereas HCPs considered pain the greatest barrier (50% vs 38% of patients). Both patients (59%) and HCPs (81%) considered pain to be a common barrier to undertaking everyday activities. Regarding future aspirations, 40% of patients wished to accept their RA despite the barriers it caused.Conclusion: Discrepancies between how HCPs perceived the feelings of patients with RA and how patients actually felt suggest that HCP–patient communication could be improved. This is the first study of its kind in Saudi Arabia and should help increase awareness of the difficulties and concerns of patients with RA in the Arabic world.Keywords: burden of illness, surveys, rheumatologists, health personnel, patients, quality of life